Quality indicators of endoscopic retrogated cholangiopancreatography in a level iii hospital associated with the development of post-ercp acute pancreatitis - Pérez Acuña-Medina, Katherine Alexandra (2021)
Objetive: Evaluate the association between the quality indicators for endoscopic retrograde cholangiopancreatography (ERCP) and the development of acute pancreatitis post-ERCP in “Hospital Regional Lambayeque” during the period 2016-June2017. Material and methods: observational, analytic transversal and retrospective study. Population of 539 and sample 358 patiens. The clinical histories were evaluated using a checklist of the quality indicators of the “The American Society for Gastrointestinal Endoscopy (ASGE)”. For the age were used mean and standard deviation; and for the other variables were used total frequencies and percent. The accomplishment percent of every indicator was evaluated. The association between the quality indicators and the development of pancreatitis was made using prevalence reasons (CI95%) and x2(p<0.05). Results: The mean age is 52.24+20.168, 66.5% are women. 98.3% of the ERCPs has appropriate indication; 0.3% doesn´t have informed consent, 15.38% has adequate antibiotic administration, 92.2% was made by a trained endoscopist, in the 96.9% the deep canulation was achieved, any has measurement of fluoroscopy time, in the 65.1% the stones <1cm were extracted successfully, in the 95.5% stent was placement successfully; any has a complete report; and in the 98.5% the adverse effects were documented. The rate of pancreatitis was 7%, perforation 0.6% and bleeding 2.5%. Only 3.9% has control in >14 days. Conclusions: There is no association between the quality indicators for ERCP and the development of acute pancreatitis post-ERCP. Not all the quality indicators were achieved. Post-ERCP Pancreatitis has more possibility to develop in woman and less possibility to develop in 65 or more years patients.